Muscle strength in older community-dwelling men is related to type of milk feeding in infancy - Robinson, S; Simmonds, S; Jameson, K; Syddall, H; Dennison, E; Cooper, C; Sayer, A (2012)
Background.There is a growing literature that links greater duration and exclusivity of breastfeeding to beneficial effects on adult health outcomes. Muscle growth in the neonatal period may be very sensitive to variations in early nutrition, but little is known about long-term effects of infant feeding on muscle strength. Methods.In 2,983 community-dwelling older men and women born 1931-1939, we examined the relationship between their type of milk feeding in infancy and their muscle strength in adult life. Information about milk feeding for each participant was abstracted from their infant record; grip strength was measured using a Jamar dynamometer. Results. Sixty percent (1,783) of the participants were breastfed only, 31% (926) were breast-and bottle-fed, and 9% (274) were bottle-fed only. There were no differences in type of milk feeding between men and women or according to social class at birth. Among the men studied, grip strength was related to the type of milk feeding, such that greater exposure to breast milk in infancy was associated with greater grip strength in adult life (p =. 023). This association remained after adjustment for the effects of a range of confounding influences (birthweight, infant growth, height, age at measurement, adult diet, and level of physical activity). In contrast, the type of milk feeding in infancy was not related to grip strength among the women studied (p =. 807). Conclusions .These data suggest that in men, differences in nutritional exposure in the early postnatal period may have lifelong implications for muscle strength. © 2012 The Author.